Effects of COVID-19 pandemic on psychiatric and psychological consultation-liaison contacts in a general hospital in North-East of Italy: a retrospective study - Prina, Eleonora; Marquis, Alice; Tedeschi, Federico; Rabbi, Laura; Salazzari, Damiano; Ballarin, Mario; Purgato, Marianna; Ostuzzi, Giovanni; Donisi, Valeria; Perlini, Cinzia; Rimondini, Michela; Del Piccolo, Lidia; et al. (Frontiers in Psychiatry, 2024)
Background. The COVID-19 pandemic has prompted significant changes in healthcare, particularly affecting psychiatric and psychological Consultation-Liaison (CL) services in general hospital settings.To assess the effects of COVID-19-related restrictions on utilization of psychiatric and psychological CL services in Northeast Italy during 2020, and to compare it to the use of services in the previous year (2019).Methods. The study collected data on psychiatric and psychological consultations in 2019 and 2020 from a hospital database. It categorizes consultations by type of patient (inpatient or outpatient) and referral source (hospital wards, general practitioners, other specialists). Pandemic-related restrictions were classified as "lockdown," "intermediate restrictions," and "no or reduced restrictions" based on the Covid Stringency Index (CSI). Poisson regression models were employed to analyze the data.Results. The findings reveal a significant 28% increase in the number of psychiatric and psychological consultations in 2020. Consultations for outpatients increased by 51%, while those for inpatients decreased by 11%. However, the lockdown and intermediate restriction phases were deemed responsible of a decrease of 42.9% and 19.5% in consultations respectively.Discussion. This study highlights the persistent psychological burden during the COVID-19 pandemic, alongside reduced CL services due to lockdown measures. Integrating telemedicine into these types of services becomes imperative for meeting patient needs during restrictions. These findings can inform policies and practices to improve effective mental health care delivery during and beyond pandemics. Future research should explore the impact of pandemic-related restrictions on mental healthcare across settings and clinical factors affecting service accessibility.